President’s Message: Spring Ahead - Fall Back - Waisman, Jackie (Operating Room Nurses Association of Canada Journal, 1993)
Once again, the fall season is upon us. Our busy lives seem to get even more hectic as fall kicks off the start of school, social activities, a return to full workloads and the list goes on.